THE LAND USE AND CHANGES IN THE RELIEF OF AREIA DOURADA STREAM BASIN, MARABA PAULISTA (SP): A STUDY BASED ON PRINCIPLES OF ANTHROPOGEOMORPHOLOGY - Scudeller Zanatta, Felipe Augusto [UNESP]; Lupinacci, Cenira Maria [UNESP]; Boin, Marcos Norberto (Uniao Geomorfologia Brasileira, 2015)
This paper discusses the application of techniques of geomorphological analysis through photointerpretation and fieldwork to evaluate relief changes caused by anthropogenic interventions in geomorphological processes, based on theoretical design of anthropogeomorphology and evolutionary/retrospective geomorphological cartography. We aim to recognize how much and how the various human activities have provided the formation and development of linear erosive features and modified the bottom valleys of Areia Dourada stream basin, Maraba Paulista (SP), from 1962 to 2013. The research was divided into two parts: in the first one was carried out bibliographical survey on papers about Pontal do Paranapanema region and Maraba Paulista city, that argue the physical characteristics, such as soils, geology and geomorphology, as well as agricultural, economic, political and social issues, in order to look into the natural and historical scenario in which the studied area is included; in the second moment, we used and pictured aerial photographs from 1962, on a scale of 1: 40,000, and from 2011, on a scale of 1: 50,000, on a background of field work made in 2012 and 2013, for the construction of geomorphological and land use and superficial coverage maps in these scenarios. As a result, we observed that the widespread deforestation, accompanied by the misuses related to the natural characteristics of the basin, especially for livestock and agriculture, and the badly designed country roads and highways were responsible for the increase from 136 to 530 linear erosive features and the expansion of areas of floodplain from 64.67 ha to 112.28 ha, which is a result of excessive sedimentation of bottom valleys.
Keywords: Anthropogeomorphology; Linear Erosive Features; Bottom Valleys.